2016
DOI: 10.1016/j.psychsport.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

A review of competitive sport motivation research

Abstract: a b s t r a c tObjectives: The purpose of this review was to synthesise contemporary research on competitive sport motivation (1995e2016) with a view to identifying trends and gaps in sample characteristics, research designs and analytical strategies, and classifying associated topics. Design: Narrative review. Method: Four databases were searched using a focused search strategy, leading to 63 studies that met the inclusion criteria. These were then evaluated in five sections: Theoretical Frameworks, Sample Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 92 publications
4
77
0
9
Order By: Relevance
“…By all accounts the pattern of associations between SMS subscales and outcome measures indicated that the scale preforms as expected according to SDT. Past findings have shown that intrinsic motivation is associated with positive consequences, and amotivation is associated with negative outcomes [16]. We confirmed this expectation given the significant positive associations between IM subscales and high self-related evaluations at both the contextual (physical self-worth) and global (global self-esteem) level.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…By all accounts the pattern of associations between SMS subscales and outcome measures indicated that the scale preforms as expected according to SDT. Past findings have shown that intrinsic motivation is associated with positive consequences, and amotivation is associated with negative outcomes [16]. We confirmed this expectation given the significant positive associations between IM subscales and high self-related evaluations at both the contextual (physical self-worth) and global (global self-esteem) level.…”
Section: Discussionsupporting
confidence: 86%
“…Studies focusing on applicability of the basic tenets of SDT in exercise and sports have indicated that intrinsic motivation, extrinsic motivation and amotivation are significantly associated with many important antecedents and outcomes related not only to training and performance themselves. In their recent review, Clancy et al [16] have listed topics and outcomes, which are the most frequently investigated alongside motivation in competitive athletes. Those included: motivational climate (12.7% of included research articles), burnout (12,7%), doping/substance use (9.5%), perfectionism (6.3%), injury (4.8%), and other (e.g.…”
Section: Assessing Motivation In Sport From Sdt Perspectivementioning
confidence: 99%
“…Motivation refers to the underlying causes of human behaviour. 10 While several models of motivation exist, selfdetermination theory 11 has consistently been applied to the study of perfectionism 12 . Within this framework, motivation is represented by a continuum of motivational subtypes (i.e.…”
Section: Perfectionism and Motivationmentioning
confidence: 99%
“…Although potential motivation could be measured before performance using motivation questionnaires and during performance using the highest rating of perceived exertion, methods of examining changes in motivation levels that occur during performance (e.g., in response to stressors) have not been established. Innovative motivation measures are needed for the endurance research SELF-REGULATION IN ENDURANCE SPORTS 10 context, and these could include combinations of psychophysiological measures (e.g., changes in RPE during self-paced tasks), behavioural measures (e.g., changes in power output during self-paced tasks), and qualitative data (e.g., think-aloud protocol, post-performance interview) (Clancy, Herring, MacIntyre, & Campbell, 2016). Social desirability challenges associated with self-reporting motivation (particularly without anonymity, e.g., King & Bruner, 2000) also merit consideration and innovative solutions.…”
Section: Self-regulation In Endurance Sportsmentioning
confidence: 99%